Characterisation of BOS steelmaking dust and techniques for reducing zinc contamination. (January 2014) - Steer, J.; Grainger, C.; Griffiths, A.; Griffiths, M.; Heinrich, T.; Hopkins, A.
<x content-type="archive" xml:space="preserve">Abstract</x> The basic oxygen steelmaking (BOS) process generates a significant amount of iron bearing dusts, and the recovery of these affects the economics and sustainability of the process. However, zinc contamination of the dust restricts how much can be recovered through the process. An inline sampling system was used to isokinetically sample primary BOS dust from the slurry pipe of a 248 m3 capacity BOS converter at Tata Steelworks Port Talbot (UK). The process was benchmarked with low galvanised scrap trials and control trials before investigating a new in-process zinc separation technique. This trial involved holding galvanised scrap in a hot converter purged with nitrogen, to volatilise the zinc from the primary dust system for capture in the secondary dust system, before the blow. Using this technique, the zinc contamination of the primary BOS dust was reduced by up to 52% of the initial zinc mass contained in the galvanised scrap charge.